Pengaruh Kemanfaatan, Kemudahan Penggunaan dan Promosi terhadap Keputusan Penggunaan E-Wallet OVO di Depok - Widiyanti, Wiwik (Universitas Bina Sarana Informatika, 2020)
Abstract - More online transactions are increasing, causing some new technology in the financial sector, one of which is e-wallet. There are 38 recorded e-wallets in Indonesia that have been licensed by Bank Indonesia, one of which is OVO. As the second most popular e-wallet in Indonesia OVO continues to innovate to increase the use of OVO. This study discusses the great benefits, benefits of using and promoting the decision to use OVO e-wallet by the people in Depok. This research method is quantitative descriptive, with 100 respondents using convenience sampling method. Data processing uses multiple linear analysis. This study produced significant and significant conclusions both partially and simultaneously between the variables of expediency, ease of use and promotion of the decision to use the OVO e-wallet. Keywords : expediency, ease of use, promotion, decision on use, e-wallet